Pengaruh Akupresur Terhadap Pengurangan Nyeri Kepala pada Ibu Hamil Trimester 1 di Tempat Praktek Mandiri Bidan Muarofah Surabaya - Eka Meiri Kurniyati; Arisda Candra Satriawati; Hadina Eka Camila (Fakultas Ilmu Kesehatan, 2020)
ABSTRACT is often the cause of the anxiety and discomfort of the mother while pregnant. The purpose of this study is to determine the effect of acupressure techniques to the reduction of headache pain in pregnant women in the first trimester PMB Muarofah A.Md Keb Surabaya.This study is a pre-experimental approach to one group pre test - post test. Population and sample in this study were all first trimester pregnant women with headache as many as 20 people. Sampling technique uses accidental sampling. Collecting data using observation sheets, Data analysis using Paired T test. The results showed that the distribution of respondents by pain before intervention mostly moderate pain 16 respondents (80%) and a small portion mild pain as much as 4 respondents (20%). Pain after intervention mostly mild pain as much as 10 respondents (50%) and a small percentage of moderate pain as much as one respondent (5.0%). The results of the analysis of P = 0.000The conclusion of this research that there Acupressure Technique Effect Against Pain Reduction on Maternal Head First Trimester 1 in PMB Muarofah A.Md Keb in Surabaya. Expected midwives can make acupressure massage as one of the interventions in reducing headache pain intensity in the first trimester pregnant women in health. Keyword: Headache, Acupressure, Woman pregnant